How to be Brief: Children’s and Adults’ Application of Grice’s Brevity Maxim in Production - Kazuko Yatsushiro; Uli Sauerland (Languages, 2019)
The brevity maxim of Gricean pragmatics states that unnecessary prolixity should be avoided. We report a case in which 5-year-old children’s performance conforms better to Grice’s maxim than adults’ behavior. Our data come from a semi-spontaneous German relative clause production study that we carried out with 5- and 7-year-old children as well as adults. In particular, we focus on the pragmatics of the passive predicates that were produced. These constituted about a third of both child and adult productions in items that targeted an object relative clause structure. Since the expression of the agent is syntactically optional with passive predicates, the brevity maxim predicts that the agent should only be expressed when it is informative. We compare two conditions to test this prediction: one where the agent is informative and one where it is not. We find that 5-year-old children display significantly greater sensitivity to the brevity maxim than adults do. In two follow-up studies, we show that adults’ violations of brevity cannot be explained by priming of by-phrases expressing the agent and that there is an effect of age within children as well.